Numerical simulation of turbulent boundary layers of surfaces covered with foul release and antifouling coatings (Journal of Naval Architecture and Marine Engineering, 2016)
In order to compare the frictional resistance of three kinds of ships hull coatings (Foul Release, SPC copper, SPC TBT) in the unfouled conditions, the numerical studies have been made. Simulations have been carried out for different Reynolds numbers in the range of 2.85 ×   5.5 ×  based on the plate length and flow velocity. Antifouling coatings have a larger mean roughness than Foul Release. The results have indicated that frictional resistance coefficient of Foul Release test plate is lower than SPC copper and SPC TBT test plates. The total resistance obtained by computational fluid dynamics has been compared with the experimental data and good agreement in results has been found which those have shown the ability of CFD modeling in calculating of fluid flow resistance by considering the coating characteristics.